Cenas de angústia e morte na dramaturgia filosófica de Jean-Paul Sartre, a partir da peça “A Prostituta Respeitosa” (1946): Representações de raça, classe e gênero - Jessica Ferreira Alves (2022)
This dissertation focuses on understanding the intersectional oppressions (race, class and gender), the anguish and death present in the work of the playwright and philosopher Jean-Paul Sartre, using as research object the piece The Respectful Prostitute, written in the year of 1946. The work takes place in the south of the United States, with the protagonist Lizzie, a prostitute who was traveling on a train and, therefore, witnesses a conflict that results in the murder of a black man. So, the piece directs its focus to the racial issue, which had great weight in that North American segregationist context and after the world wars. Sartre (1905-1980), as one of the precursors of existentialism in France, uses different languages to express his philosophy and political engagement. Therefore, in this research we investigate the aesthetic aspects of the play, through bibliographical analysis and the dramaturgical text, and thinking about how Jean-Paul Sartre, in the theatrical text, put in perspective the oppressions of race, class and gender in his works, emphasizing the theme of death and anguish. KEYWORDS: Sartre, representation, problems of gender, race, class, existentialism, dramaturgy.